Use of Ceftazidime-Avibactam in Children Admitted to Pediatric Intensive Care Units - André Ricardo Araujo da Silva; Rafael Quijada (MDPI AG, 2024)
Background: Ceftazidime-Avibactam (CAZ-AVI) is one of the new antibiotics available to treat infections due to carbapenem-resistant gram-negative bacteria (CRB). Our aim was to describe the use of CAZ-AVI in children admitted to pediatric intensive care units (PICUs), with suspected or proven CRB infections. Methods: A retrospective descriptive study was conducted in two PICUs of Rio de Janeiro, Brazil, between January 2020 and January 2024. Children aged 0 to 18 years who received CAZ-AVI for more than 24 h were included. Results: CAZ-AVI was used in 37 patients. The median age was 28 months (range 1-215), 17 (45.9%) being male. The median time from the patient admission to the initial prescription of CAZ-AVI was 39.9 days (range 1-138). Thirty-four (91.9%) children had at least one comorbidity at admission and (91.9%) used at least one invasive device prior to the CAZ-AVI prescription, and 89.2% had received carbapenem before; and fifteen (40.5%) had healthcare-associated infection (HAI) prior to CAZ-AVI use. The mean time of CAZ-AVI use was 11 days (range 1-22). Gram-negative bacteria were isolated in cultures from 12 (32.4%) patients in the 24 h prior to prescription or on the day of prescription. In five patients, CRB was confirmed in cultures, and in four (80%) of them, microbiological clearance was verified after 7 days of treatment. The 30-day mortality rate was 37.8%. Conclusion: Almost all patients who used CAZ-AVI were critically ill children with multiple comorbidities and previous use of carbapenems. Among CRB confirmed infections, microbiology clearance in 7 days was high.